The theoretical perspectives underlying technology transfer: a literature review - Sazali Abdul Wahab; Raduan Che Rose; Suzana Idayu Wati Osman (2012)
The main objective of this paper is to contribute to the existing technology transfer literature by comprehensively reviewing and outlining the theories underpinning technology transfer. This review could stimulate and generate dynamic ideas for future researchers i.e. to further identify, conceptualize and understand the theories and perspectives underlying technology transfer. Such strong understanding is necessary to enable the interested parties (such as private sectors, government departments, academics, researchers and students) to relate these theories with the practical and empirical aspects of various technology transfer models, mechanism, issues and challenges. This is due to the fact that different perspectives/theories underlying technology transfer will have different theoretical arguments and insights, research problems, constructs, variables, and measurements. The literatures on technology transfer and international technology transfer are extensive, varied in perspective and from many disciplines; which include political science, economics, sociology, public policy, marketing and management. Since technology transfer literatures cover wide research areas, therefore this paper sets its perimeter by focusing only on the theories and perspectives underlying intra and inter-firm technology transfer